Numerical Simulation and Diagnosis of a Precipitation in Qilian Mountains under the Coupling of Upper and Lower Systems - Qiang JIANG; LinBo WEI; Chao LI; Yan LI; HongYu WANG (Gaoyuan qixiang)
Based on ERA5 reanalysis data and CLDAS land grid precipitation data from the National Meteorological Information Center， a systematic WRF numerical simulation and precipitation mechanism diagnosis of a typical systematic precipitation process in the Qilian Mountains are carried out in this paper.The dynamic diagnosis results of the circulation background field show that the interaction between the mesoscale upper trough system and the local lower flow around and flow over provides important dynamic conditions.The mesoscale dynamic uplift in front of the trough caused by the development of the upper trough determines the distribution of the heavy precipitation belt during the precipitation process， while the lower flow around and flow over provide direct dynamic conditions for local heavy precipitation.The further diagnosis results of water vapor transport and budget show that the water vapor source of this precipitation mainly comes from the Sichuan Basin.The flow around will transport abundant water vapor for the precipitation area in front of the windward slope， and the flow over will promote the reverse gradient transport of water vapor along the terrain height and converge near the precipitation center.In the stage of heavy precipitation， the vertical transport of water vapor contributes the most to the water vapor budget， followed by the convergence of water vapor， and the local variation of water vapor can be basically ignored.Finally， the diagnostic results of atmospheric stratification characteristics show that when both atmospheric dynamic conditions and water vapor conditions are conducive to precipitation， combined with the enhancement of the instability of low and medium tropospheric stratification， it is easier to trigger convection and enhance precipitation in front of the windward slope.